2021
DOI: 10.1371/journal.pone.0251908
|View full text |Cite
|
Sign up to set email alerts
|

Applying the RE-AIM framework in a process evaluation of the introduction of the Non-Pneumatic Anti-Shock Garment in a rural district of Zimbabwe

Abstract: The Non-Pneumatic Anti-Shock Garment (NASG) is a first aid tool that can halt and reverse hypovolemic shock secondary to obstetric hemorrhage. The World Health Organization recommended the NASG for use as a temporizing measure in 2012, but uptake of the recommendation has been slow, partially because operational experience is limited. The study is a process evaluation of the introduction of NASG in a public sector health facility network in rural Zimbabwe utilizing an adapted RE-AIM, categorizing observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Despite this gap among the study facilities, access to emergency transport for referral of patients was widely available, and this transportation was utilized to carry out NASG rotation, providing referring facilities with a clean NASG when they sent a patient wrapped in one. This lack of logistical challenge for NASG rotation relative to experience reported from other countries is worth noting [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this gap among the study facilities, access to emergency transport for referral of patients was widely available, and this transportation was utilized to carry out NASG rotation, providing referring facilities with a clean NASG when they sent a patient wrapped in one. This lack of logistical challenge for NASG rotation relative to experience reported from other countries is worth noting [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of observational studies showed a 48% mortality reduction among women who received the NASG, compared to the standard of care [ 6 ]. A process evaluation of the introduction of the NASG in public sector facilities in Zimbabwe showed healthcare workers were able to correctly use the garment after training and the public health system could afford to incorporate and maintain its use [ 7 ]. In cases of hypovolemic shock where a NASG was used, there were no maternal deaths and no extreme adverse outcomes, however, because the implementation period used in this evaluation was not of sufficient duration to estimate public health impact and was carried out in one country, a similar process evaluation of a longer period in a different geography enhances value of the literature on incorporation of NASG in LMIC maternity services.…”
Section: Introductionmentioning
confidence: 99%